A review on different control techniques using DSTATCOM for distribution system studies - K. Swetha; V. Sivachidambaranathan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper focus on distribution system by applying different control techniques in order to improve the performance of the system. In the distribution system mainly concentrate on power quality issues like reactive power control, harmonic elimination, power factor correction, etc. Because of power quality problems voltage, current, frequency are continuously changing in power systems. These changes will effects the performance of power systems. Power quality problems can be compensated by placing DSTATCOM which is connected at PCC in parallel. It is shunt connected VSI along with the filters, with the help of DSTATCOM voltage sag, swell and THD can be controlled. This paper presents detailed explanation about performance and configuration of latest control techniques to control the DSTATCOM.